The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s1516-14392013005000007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cadmium(II) and Lead(II) ions from aqueous phase on sodic bentonite

Abstract: This paper describes the adsorption of Cd 2+ and Pb 2+ ions using sodic bentonite clay type Fluidgel modified. The Fluidgel before and after chemical modification and thermal activation was characterized by different techniques including X-ray diffraction, thermal analysis, Fourier transform infrared, surface area, helium pycnometry, cation exchange capacity and scanning electron microscopy. Pseudo-first order, pseudo-second order and intra-particle diffusion models were used to analyze the kinetic curves. Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Ion exchange can be an additional process for removal of copper and lead by RHA, being verified by the results of chemical composition presented in Table 8, where the percentage of exchangeable potassium in the RHA drastically decreased after adsorption. The mechanism of ion exchange can be written as follows: Similar results were obtained by Galindo et al (2013) in a study of the removal of cadmium and lead using sodic clay. The authors reported that ion exchange can be an additional process for removal of cadmium and lead on sodic clay and that the amount of exchangeable cations Na + was reduced after metal adsorption.…”
Section: Scanning Electron Microscopymentioning
confidence: 57%
See 1 more Smart Citation
“…Ion exchange can be an additional process for removal of copper and lead by RHA, being verified by the results of chemical composition presented in Table 8, where the percentage of exchangeable potassium in the RHA drastically decreased after adsorption. The mechanism of ion exchange can be written as follows: Similar results were obtained by Galindo et al (2013) in a study of the removal of cadmium and lead using sodic clay. The authors reported that ion exchange can be an additional process for removal of cadmium and lead on sodic clay and that the amount of exchangeable cations Na + was reduced after metal adsorption.…”
Section: Scanning Electron Microscopymentioning
confidence: 57%
“…Some of the important ones include zeolites (Wang and Peng, 2009;Okolo et al, 2000), activated carbon (Wahby et al, 2011;Moreno-Piraján et al, 2011;Attia et al, 2010;Giraldo and Moreno-Piraján, 2008), rubber ash (Mousavi et al, 2010), clay (Galindo et al, 2013;Almeida Neto et al, 2012;Vieira et al, 2010a;Vieira et al, 2010b), expanded perlite (Torab-Mostaedi et al, 2010), vermiculite (Nishikawa et al, 2012), algae (Vieira et al, 2008;Vijayaranghavan et al, 2005;Silva et al, 2003), bacteria (Yilmaz et al, 2010), coir pith (Parab et al, 2006), sugarcane bagasse (Lv et al, 2008;Gupta and Ali, 2004), olive stone (Calero et al, 2009) and rice husks Vieira et al, 2011;Senthil Kumar et al, 2010;Naiya et al, 2009;Srivastava et al, 2006;Ye et al, 2010;Nakbanpote et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…Equilibrium for the adsorption of cobalt ions onto the bentonite was attained after 60 minutes with initial concentrations of 240 mg l -1 at 60 °C. Thus an equilibrium was attained is shorter time interval in comparison to the equilibrium time of 150 [32] and 120 minutes [33] reported for cadmium removal.…”
Section: Xrdmentioning
confidence: 63%
“…Low-cost materials such as agricultural waste, chitosan, clays, seaweed, macrophytes, industrial waste processing have been used to evaluate the removal of heavy metal ions from wastewater (Lee and Davis, 2001;Hassanein and Koumanova, 2010;Ngah et al, 2002;Galindo et al, 2013;Almeida Neto et al, 2012;Matos et al, 2009;Lima et al, 2013). Among these materials, macrophytes have shown good affinity with metal ions, and are renewable in nature (Banerjee and Sarker, 1997;Saygideger et al, 2005;Phetsombat et al, 2006;Rahman et al, 2008;Khellaf e Zerdaoui, 2010).…”
Section: Introductionmentioning
confidence: 99%